Heteroatom‐Driven Coordination Fields Altering Single Cerium Atom Sites for Efficient Oxygen Reduction Reaction - Yin, Leilei; Zhang, Shuai; Sun, Mingzi; Wang, Siyuan; Huang, Bolong; Du, Yaping (Advanced materials (Weinheim), 2023)
For current single‐atom catalysts (SACs), modulating the coordination environments of rare‐earth (RE) single atoms with complex electronic orbital and flexible chemical states is still limited. Herein, cerium (Ce) SAs supported on a P, S, and N co‐doped hollow carbon substrate (Ce SAs/PSNC) for the oxygen reduction reaction (ORR) are reported. The as‐prepared Ce SAs/PSNC possesses a half‐wave potential of 0.90 V, a turnover frequency value of 52.2 s−1 at 0.85 V, and excellent stability for the ORR, which exceeds the commercial Pt/C and most recent SACs. Ce SAs/PSNC‐based liquid zinc–air batteries (ZABs) exhibit a high and stable open‐circuit voltage of 1.49 V and a maximum power density of 212 mW cm−2. As the catalyst of the air cathode, it also displays remarkable performance in flexible electronic devices. Theoretical calculations reveal that the introduction of S and P sites induces significant electronic modulations to the Ce SA active sites. The P and S dopings promote the electroactivity of Ce SAs and improve the overall site‐to‐site electron transfer within the Ce SAs/PSNC. This work offers a unique perspective for modulating RE‐based SACs in a complex coordination environment toward superior electrocatalysis and broad applications in energy conversion and storage devices. Through ubtle modulation of the coordination environments by introducing P and S heteroatoms, the Ce electroactive sites are modulated to achieve effective enhancement of the oxygen reduction reaction's intrinsic catalytic activity. This work supplies significant references for optimizing the electroactivity of atomic catalysts by a coordination regulation strategy.